The staggering rise of the South? - Yılmaz Akyüz (South Centre, 2012)
This paper argues that the unprecedented acceleration of growth in the developing world in the new millennium in comparison with advanced economies is due not so much to improvements in underlying fundamentals as to exceptionally favourable global economic conditions, shaped mainly by unsustainable policies in advanced economies. The only developing economy which has had a major impact on global conditions, notably on commodity prices, is China. However, growth in China has been driven first by a rapid expansion of exports to advanced economies and more recently, after the global crisis, by an investment boom, neither of which is replicable or sustainable over the longer term. To maintain a rapid growth, export-led Asian economies need to reduce their dependence on foreign markets. For Latin American and African commodity exporters, gaining greater autonomy and achieving rapid and stable growth depend on their success in reducing reliance on capital flows and commodity earnings - the two key determinants of their growth which are largely beyond national control.
Keywords: 300